Governance violations and their impact on business growth: A case study of Sharia Rural Bank Saka Dana Mulia Kudus - Sumarno, Sumarno; Yahya, Muchlis; El Junusi, Rahman; Murtadho, Ali; Elizabeth, Misbah Zulfa; Abdullah, Irwan (Universitas Islam Indonesia, 2026)
IntroductionGovernance failure in Islamic rural banking remains a critical challenge because weak implementation of prudential principles, ineffective oversight, and inadequate risk management can threaten institutional sustainability and ultimately result in the revocation of an operating license. Although governance has been extensively discussed in Islamic banking, comprehensive evidence explaining how governance violations, liquidity risk, and capital inadequacy jointly contribute to institutional failure remains limited, particularly among Sharia Rural Banks in Indonesia.ObjectivesThis study aims to identify the types of governance violations that occurred at Sharia Rural Bank Saka Dana Mulia Kudus, analyze the implementation of good corporate governance and Islamic corporate governance, examine the relationship between governance failure, liquidity risk management, and minimum capital adequacy, and evaluate their impact on sustainable business growth.MethodThis study employed a qualitative approach using a single-case study design focusing on Sharia Rural Bank Saka Dana Mulia Kudus. Secondary data were collected from regulatory documents, banking publication reports, financial statements, official policies, media reports, and academic literature covering the period from 2020 to 2024. Document analysis, thematic coding, and source triangulation were applied to identify governance failures, liquidity risk, capital adequacy issues, and their consequences for banking performance and business continuity.ResultsThe findings reveal that governance failure resulted from the ineffective performance of the board of directors and board of commissioners, weak implementation of prudential principles, inadequate liquidity risk management, failure to satisfy minimum capital adequacy requirements, and ineffective Sharia compliance oversight. These weaknesses caused severe deterioration in financial performance, reflected by extremely high non-performing financing, declining profitability, insufficient liquidity reserves, negative capital adequacy, and continuing operating losses. The resulting decline in depositor confidence, reduction in third-party funds, unsuccessful restructuring efforts, and worsening financial health ultimately led to the revocation of the bank’s operating license and significantly hindered business growth.ImplicationsThe findings emphasize the importance of strengthening governance structures, improving liquidity risk management, ensuring sustainable capital adequacy, enhancing the effectiveness of the Sharia Supervisory Board, and implementing more proactive regulatory supervision and early warning mechanisms to safeguard institutional stability and promote sustainable growth in Islamic rural banking.Originality/NoveltyThis study provides a comprehensive analytical framework integrating governance failure, liquidity risk management, minimum capital adequacy, and Islamic corporate governance to explain institutional failure in a Sharia Rural Bank. It offers practical early warning indicators for regulators and banking practitioners while demonstrating that Islamic institutional identity alone does not guarantee effective governance without substantive oversight, prudent management, and integrated risk control.